2011
DOI: 10.4314/ajfand.v11i5.70449
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and sensory profiling of the African giant land snail fed commercial-type and leaf-based diets in a rain-forest ecology

Abstract: Nutritional and organoleptic properties of the African giant land snails (Archachatina marginata) were investigated using 96 healthy-looking growing snails maintained on broiler starter mash (BSM) as control, Talinium triangulare or waterleaf, Centrosema molle or centro leaves, and Carica papaya or pawpaw leaves for 16 weeks. This study was set up as a completely randomized design (CRD) with the snails allocated to 4 treatment groups (broiler starter mash (BSM) as control; Talinium triangulare leaves or waterl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 2 publications
1
6
3
Order By: Relevance
“…The crude protein value of pawpaw leaves obtained in this study indicates it as a rich source of protein and therefore, could serve as a good source of protein supply for weaner rabbits. Several authors (Omole et al 2004;Onyimonyi and Onu 2009;Babalola and Akinsoyinu 2010;Kalio and Etela 2011) have reported higher crude protein values than that obtained in our study, and this could be attributed to differences in the age of the plant and soil nutrient.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…The crude protein value of pawpaw leaves obtained in this study indicates it as a rich source of protein and therefore, could serve as a good source of protein supply for weaner rabbits. Several authors (Omole et al 2004;Onyimonyi and Onu 2009;Babalola and Akinsoyinu 2010;Kalio and Etela 2011) have reported higher crude protein values than that obtained in our study, and this could be attributed to differences in the age of the plant and soil nutrient.…”
Section: Discussioncontrasting
confidence: 83%
“…Pawpaw leaves are rich in proteins with reported crude protein values ranging between 23.9 and 33.3 % (Omole et al 2004;Babalola and Akinsoyinu 2010;Kalio and Etela 2011), and they could be particularly suitable for small holder rabbit production. Pawpaw leaves have also been reported to contain some biologically active compounds, one of which is papain, which aids in digestion (Barger et al 2009;Ikeyi et al 2013;Macalood et al 2013).…”
Section: Introductionmentioning
confidence: 97%
“…This is close to the result (12.2 mg/100 g) obtained by [16]. However, the value obtained was not different from 16.1 mg/100g reported by Kalio, et al [15]. Wosu [16] reported that iron content of snail varies from one locality to another depending on mineral content of the soil in which these snails are raised.…”
Section: Chemical Composition Of Snail Meat Productssupporting
confidence: 89%
“…From the analysis of variance the seasoned smoke-dried product was significantly different (P<0.05) from other products and had the highest mineral content. The value obtained for P (235.0 mg/100 g) was not different from the value (238.0 mg/100 g) obtained by Kalio, et al [15]. Phosphorus and potassium are important in human and animal nutrition.…”
Section: Chemical Composition Of Snail Meat Productscontrasting
confidence: 49%
“…Snails are popular protein sources consumed by people worldwide, Apart from being a protein source, they are a good source of iron, calcium, and phosphorus, and are said to contain almost all the amino acids needed by humans [1]. The species of land snails commonly sold in Port Harcourt and other coastal towns in Nigeria is Archachatina marginata, also known as the African giant land snail [2,3]. The African giant land snails are mostly found in the forest, farms and gardens where they have unlimited vegetation to feed on.…”
Section: Introductionmentioning
confidence: 99%